Conquest XHTML: a programers guide to extensible HyperText Markup Language - Olanrewaju, Rashidah Funke; Habaebi, Mohamed Hadi; Khan, Burhan Ul Islam (Google GRIN Verlag, 2013)
Document from the year 2013 in the subject Computer Science - Technical Computer Science, grade: B SC IT, International Islamic University (Khulliyah of Engineering), course: Web Technologies, language: English, abstract: Evolution of HTML has virtually come to with the emergence of XHTML. According to the W3C, "XHTML 1.0 is a reformulation of HTML 4.01 in XML, and combines the strength of HTML 4 with the power of XML." The book among few of its kind in Web Technologies that use a Top-Bottom approach, which makes the process of learning the technology much easier for the reader, & the reader can clearly comprehend the reason of evolution of the same....